Cold stress induces differential gene expression of retained homeologs in Camelina sativa cv Suneson - Fang, Chao; Hamilton, John P.; Vaillancourt, Brieanne; Wang, Yi-Wen; Wood, Joshua C.; Deans, Natalie C.; Scroggs, Taylor; Carlton, Lemor; Mailloux, Kathrine; Douches, David S.; Nadakuduti, Satya Swathi; Jiang, Jiming; et al. (Frontiers in Plant Science, 2023)
Camelina sativa (L.) Crantz, a member of the Brassicaceae, has potential as a biofuel feedstock which is attributable to the production of fatty acids in its seeds, its fast growth cycle, and low input requirements. While a genome assembly is available for camelina, it was generated from short sequence reads and is thus highly fragmented in nature. Using long read sequences, we generated a chromosome-scale, highly contiguous genome assembly (644,491,969 bp) for the spring biotype cultivar ‘Suneson’ with an N50 contig length of 12,031,512 bp and a scaffold N50 length of 32,184,682 bp. Annotation of protein-coding genes revealed 91,877 genes that encode 133,355 gene models. We identified a total of 4,467 genes that were significantly up-regulated under cold stress which were enriched in gene ontology terms associated with ‘response to cold’ and ‘response to abiotic stress’. Coexpression analyses revealed multiple coexpression modules that were enriched in genes differentially expressed following cold stress that had putative functions involved in stress adaptation, specifically within the plastid. With access to a highly contiguous genome assembly, comparative analyses with Arabidopsis thaliana revealed 23,625 A. thaliana genes syntenic with 45,453 Suneson genes. Of these, 24,960 Suneson genes were syntenic to 8,320 A. thaliana genes reflecting a 3 camelina homeolog to 1 Arabidopsis gene relationship and retention of all three homeologs. Some of the retained triplicated homeologs showed conserved gene expression patterns under control and cold-stressed conditions whereas other triplicated homeologs displayed diverged expression patterns revealing sub- and neo-functionalization of the homeologs at the transcription level. Access to the chromosome-scale assembly of Suneson will enable both basic and applied research efforts in the improvement of camelina as a sustainable biofuel feedstock.